Factors Influencing Non-Green Hotels to Adopt Green Practice: Small Hotels in Thailand Active Beach Cluster - Chiangphan, Narinsiree (Connexion: Journal of Humanities and Social Sciences, 2023)
This study analyzed the impact of factors on the adoption of green practices among non-green hotels in Thailand active beach cluster (Chonburi, Rayong, Chanthaburi, and Trat). Primary data were collected from a sample of 318 non-green hotel owners and managers using a proportionate stratified sampling method. Exploratory factor analysis (EFA) was employed to group the variables, and multiple regression analyses were conducted to analyze the data. To analyze the attribute of green factors of small hotel in Thailand (Objective 1), EFA was conducted and revealed that the factors can be categorized into four groups: (1) Green Strategic Management (innovative and energy-efficient technologies, cost allocation for environment activities, effective marketing, investment in infrastructure and system, and strategic planning), (2) Leadership (owner’s awareness, perceived green standard and green law, and environmental leadership), (3) Key-Partner (clear organizational identity, partner, supplier, and hotel guests’ awareness), and (4) Employee Empowerment (green knowledge, employee adaptability, rewards and incentive, and facilities and resources). This classification accounts for 71.781% of the total variance. To analyze the influences of green factors to green practices of small hotel in Thailand (Objective 2), multiple regression was analyzed and indicated that all four groups (EFA result) of factors are significantly associated with green practices of small hotels; Key-Partner, Employee Empowerment, Green Strategic Management, and Leadership, are significant predictors of green practices, explaining varying percentages of the practice’s variance: 29.9%, 27.4%,15.5%, and 1.5% respectively. The study suggests that hoteliers of small hotel should prioritize promoting an understanding of natural resource usage among employees and stakeholders which can be achieved through training programs, awareness campaigns, and effective communication strategies. Additionally, hotels should integrate green practices into their marketing strategies, finances, and operational plans to ensure that green practice is an integral part of their business model. As a result, hotels can successfully implement green practices and contribute to both environmental sustainability and business profitability.